¿Cuento contigo? La estabilidad en la gestión de César Álvarez (2006-2013) - Arévalo León, Rosa (2015)
This article analyzes the factors that contributed to Cesar Alvarez’s administration stability as regional president of Ancash during almost two full consecutive terms (2006 – 2013). Thus, the research focuses on the development of clientelistic and patronage networks that strength- ened his ties with citizens, providing him with constant support. Moreover, those practices protected him from any act of fiscalization or investigation. Finally, public spending, largely financed with mining canon, made possible for Alvarez to show himself as an efficient regional president by developing major infrastructure projects in the region.